OPTIMASI KONSENTRASI POLIVINIL PIROLIDON (PVP) SEBAGAI BAHAN PENGIKAT TEHADAP SIFAT FISIK TABLET EKSTRAK ETANOL RIMPANG BANGLE (Zingiber cassumunar Roxb) - devi, ida ayu sintha (Jurnal Farmasi Udayana; Vol. 7 No. 2, Tahun 2018DO - 10.24843/JFU.2018.v07.i02.p02, 2018)
Zingiber cassumunar Roxb contains active compounds such as cassumumin AC, cassummarin AC, phenylbutanoid , and (E) -4- (3,4-dimethoxyphenyl) but-3-en-1-ol which has activities as anti-inflammatory, antioxidant and anti-allergenic agents so that they are potentially used as anti-allergies. Zingiber cassumunar Roxb is made into tablet because it has several advantages, which are easy to consume, practical, the right amount, cover the bitter taste and the distinctive smell and its stability is maintained in storage. This study aims to produce Zingiber cassumunar Roxb tablets that have good physical properties by using PVP as a binder. Zingiber cassumunar Roxb extract was made by maceration using 70% ethanol solvent, the tablet was formulated using wet granulation method. Zingiber cassumunar Roxb ethanol extract tablet was formulated in 3 formulas with variations in the PVP FI content of 1%, FII 2.75%, and FIII 4.5%. The resulting granules were tested for physical properties including moisture test, particle size distribution, flow time, stationary angle, bulk density, and compressibility, while the tablets produced were tested for physical properties including organoleptic test, uniformity of size, uniformity of weight, friability, and disintegration time. The results showed that the optimum concentration obtained was at FIII with 4.5% PVP concentration that complied the organoleptic test requirements, uniformity of size, weight uniformity, and fragility of tablets.